2001
DOI: 10.2307/3558449
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression under intraspecific competition in a highly outcrossing population of Crepis sancta (Asteraceae): evidence for frequency‐dependent variation

Abstract: Inbreeding depression is a major selective factor acting to maintain outcrossing in hermaphroditic plants. Recently it has been shown that environmental conditions may greatly affect the levels of inbreeding depression. In this study, the effects of intraspecific competition, from either crossed or inbred progeny, and plant density on the expression of inbreeding depression were estimated for the allogamous colonizing plant Crepis sancta (Asteraceae). The population used in this experiment showed a very high o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
(39 reference statements)
3
26
0
Order By: Relevance
“…Both results are consistent with a magnifying effect on ID in harsh environmental conditions similar to that observed for other taxa (Latter and Mulley, 1995;Haag et al, 2002). In plants, Cheptou et al (2001) found that ID on survival was greatest when inbred plants compete with outbred plants. However, as reviewed by Keller and Waller (2002), ID is not universally higher in stressful environments, suggesting that generalisation should be avoided.…”
Section: Discussionsupporting
confidence: 88%
“…Both results are consistent with a magnifying effect on ID in harsh environmental conditions similar to that observed for other taxa (Latter and Mulley, 1995;Haag et al, 2002). In plants, Cheptou et al (2001) found that ID on survival was greatest when inbred plants compete with outbred plants. However, as reviewed by Keller and Waller (2002), ID is not universally higher in stressful environments, suggesting that generalisation should be avoided.…”
Section: Discussionsupporting
confidence: 88%
“…This could imply that the loss in competition depends more so on the type of competitor, than on how strong the level of competition is. This is comparable to findings in plants; the negative effects of inbreeding are most noticeable when inbred plants are competing directly with outbred plants (Cheptou et al., ; Koelewijn, ). Moreover, Cheptou et al.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, Cheptou et al. () found that the type of competitor (inbred or outbred plant) was even more important for inbreeding depression than the number of competitors. If we can indeed extrapolate these findings in plants to our findings in birds, and inbred birds lose when they compete with outbred birds regardless of (dis)advantageous conditions, this would be an important factor to consider in the future (vertebrate) animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…This might, in turn, alleviate inbreeding depression (Cheptou & Donohue ; but see Willi, Dietrich & van Kleunen ). Although empirical studies on plants show that reduced intraspecific competition can weaken inbreeding depression (Schmitt & Ehrhardt ; Wolfe ; Pujol & McKey ) others have not detected this effect (Eckert & Barrett ; Cheptou, Lepart & Escarré ) or found it to be inconsistent (Van Treuren et al . ).…”
Section: Evolution Of the Mating System Across Geographic Ranges As Pmentioning
confidence: 99%